Study of integration 2.4GHz and 5.8GHz in RFID tag - Hazry, Desa; Mohd Sofian, Muhammad Rosbi; Shaiful, Zairi (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.